The Variety in the Common Theme of Translation Inhibition by Type II Toxin–Antitoxin Systems - Jurėnas, Dukas; Van Melderen, Laurence (Frontiers in Genetics, 2020)
Type II Toxin-antitoxin (TA) modules are bacterial operons encoding a toxic protein and its antidote that form a self-regulating genetic system. Antitoxins put halter on toxins in many ways that distinguish different types of TA modules. In type II TA modules, toxin and antitoxin are proteins that form a complex that physically sequesters the toxin, thereby preventing its toxic activity. The factors releasing the toxin from the complex are still under debate and are directly related to the question of function(s) of TA modules. Type II toxins inhibit various cellular processes; however, the translation process appears to be their favorite target and nearly every steps of this complex process are being inhibited by type II toxins. The structural features, enzymatic activities and target specificities of the different toxin families are discussed. Finally, this review emphasizes that the structural folds presented by these toxins are not restricted to type II TA toxins or to one particular cellular target and discusses why so many of them evolved to target translation as well as the recent developments regarding the role(s) of these systems in bacterial physiology and evolution.